Karakteristik Morfologik dan Morfometrik Spermatozoa Ayam Nunukan - Fikri Ardhani (Jurnal Peternakan, 2018)
The fertility of a rooster is not only influenced by motility, viability and DNA integrity of the spermatozoa but also by the morphological integrity of the spermatozoa. The objective of the study was to determine the morphological and morphometric description of spermatozoa in Nunukan rooster, one of Indonesian germplasm. Rooster’s semen was collected with dorso-abdominal massage method. The semen was stained with a combination of Eosin and Nigrosin prior to the observation of the morphologic and morphometric parameters. A microscope with 100 times magnification, as many as 100 spermatozoa, was used to evaluate the morphologic aspects. Hereafter, the morphometric aspects were analyzed using the Raster Image program to identify the head dimension, the head length and width, the mid-piece length, the tail length, and the ratio of the head and tail. The spermatozoa of Nunukan rooster showed the average total length of 86.724±12.496 μm. Furthermore, the head length, the mid-piece length and the tail length are 12.766±2.307 μm, 4.220±1.127 μm, and 75.738 ± 9.061 μm, respectively, while the head width is 1.391±0.244 μm. On the other hand, the ratio of head length and the tail lenght is 1: 5.9. The morphologic normal percentage is 80.50±9.40%. In conclusion, the characteristics of spermatozoa of Nunukan rooster due to the aspects of morphologic, morphometric and morphologic normal percentage are within the range of other types of rooster in many previous studies.